Imaging Lesions of the Lateral Hip - Pan, Judong; Bredella, Miriam A. (Seminars in Musculoskeletal Radiology, 2013)
The lateral aspect of the hip is composed of a complex array of osseous and soft tissue structures. Both common and uncommon clinical entities are encountered in the lateral hip. This article briefly introduces fundamental imaging anatomy and the functional roles of different osseous and soft tissue structures in the lateral aspect of the hip, followed by a discussion of relevant imaging findings of lateral hip pathology. Greater trochanteric pain syndrome is frequently encountered in patients with lateral hip pain and encompasses a spectrum of soft tissue abnormalities including trochanteric and subgluteal bursitis, and tendinopathy or tears of the gluteal tendons. In addition, different types of injuries to the gluteal myotendinous unit and injuries to the indirect head of the rectus femoris, proximal iliotibial band, and the lateral joint capsular ligaments can present with lateral hip pain. Some of the less common soft tissue abnormalities of the lateral hip include Morel-Lavallée lesion and meralgia paresthetica.
Keywords: lateral hip; greater trochanteric pain syndrome; proximal iliotibial band; Morel-Lavallée lesion; meralgia paresthetica